Особливості прогнозування теплового розширення листового скла різної товщини - Жеплинський, Тарас Богданович; Курій, Анастасія Олегівна (НТУ "ХПІ", 2016)
Виявлено помилку у співвідношенні між об‘ємним і лінійним температурним розширенням скла. Замість β = 3α, потрібно використовувати β = α³ · ∆Τ². В інтервалі температур 20-150 ºС ТКЛР флоат-скла поступово збільшується, а далі залишається незмінним. В інтервалі склування ТКЛР стрімко зростає до певного максимуму. Видовження 3-мм скла більше ніж 4-мм, однак 4-мм скло характеризується більшим значенням максимальної величини ТКЛР.

The error in the ratio between the volumetric and the linear thermal expansion of glass was found. Instead β = 3α it should be used β = α³ · ∆Τ². The research of thermal expansion features of 3 and 4 mm float glass was conducted. The measurement of TCLE (thermal coefficient of linear expansion) was carried out using a vertical quartz dilatometer at samples of 50×10 mm. It was found that in the temperature interval of 20-150 °C TCLE of float glass gradually increases (from 77 ⋅ 10⁻⁷ to 92 ⋅ 10⁻⁷ °C⁻¹ for 3 mm glass and from 75 ∙ 10⁻⁷ to 90 ⋅ 10⁻⁷ °C⁻¹ for 4 mm one) and remains unchanged. In the glass transition interval TCLE increases rapidly to a certain maximum. The lengthening of 3 mm glass is greater than 4 mm one, but 4 mm glass is characterized by higher values of maximum TCLE and is equal to 221 ⋅ 10⁻⁷ °C⁻¹ (for 3 mm glass this value is 182 ⋅ 10⁻⁷ °C⁻¹).
Features of thermal expansion prediction of float glass of different thickness
Keywords: ТКЛР; флоат-скло; криві дилатометричні; видовження; температура; склування; дилатометр; TCLE; float glass; dilatometer curves; lengthening; glass transition temperature; dilatometer